Perceived Parenting Styles and Psycho-social Wellbeing of Nigerian Adolescents - Akpunne, Bede; O Akinnawo, Ebenezer; A Olajide, Olufunmilayo (International Journal of Scientific Research and Management (IJSRM), 2020)
The influence of parenting styles on the psychosocial wellbeing of Nigerian adolescents is yet of be given adequate research attention. This study bridges the gap in knowledge. Findings may be useful in planning appropriate interventions program necessary to improve the psychosocial wellbeing of adolescents in Osun state, southwestern Nigeria and relation with similar social-cultural backgrounds. Purposive sampling technique was used to select 332 (mean age = 14) in-school adolescents who responded to Mental Health Continuum – Short Form (MHS-SF) and Parenting Style Instrument (PSI). Descriptive and inferential statistics (Regression, Independent sample t-test and One Way ANOVA) were used for data analysis. A low level of psychosocial wellbeing was observed among the adolescents. Prevalence of very low levels of emotional wellbeing (16.9%), social wellbeing (22%), and psychological wellbeing (19.3%) were reported. Patterns of observed parenting styles are authoritative parenting style (45.5%, 41.6%, and 12.9%), authoritarian parenting style (53%, 30.7% and 16.3%); permissive parenting style (64.2%, 20.7% and 15.1%)  for low, high and very high levels respectively. No significant gender difference was observed in the psychosocial wellbeing scores of the adolescents; a significant religious affiliation difference was found in the social wellbeing of the participants. Adolescents from public schools manifested higher levels of social wellbeing than their counterparts from private schools. Parenting styles significantly predict level of psychosocial wellbeing of the adolescents. Neither family type nor family size had significant influence on the level of psycho-social wellbeing of the adolescents.